UUM Web-Based Computer Laboratory Reservation System : A Prototype - Rochin, Demong (2003)
Online computer laboratory reservation system is a system that has been implemented to many education institutions especially at university level. This develop system is implemented using web-based application because it gives many benefits. the increment of the computer laboratory user's it generates inssufficient computer distribution among the user in the computer laboratory. Therefore, the purpose of this prototype computer laboratory reservation system through web is to solve this problem and in addition it also will ease the management in updating the reservation record. Methodology used to developed the system is Object Modeling Technique (OMT) that consist of five phases namely analysis, system design, object design, implementation and testing Database used to developed the system is MySQL with PHP programming language. Apache server will be use a server to run the system and Internet Explorer 6.0 as a web browser of the system. The main benefit of the prototype system is the user can view the availability of the PC at anytime and fro anyshere during reservation. This system is enable to save time and cost.